Infant mortality by color or race from Rondônia, Brazilian Amazon - Gava, Caroline; Cardoso, Andrey Moreira; Basta, Paulo Cesar (Revista de Saúde Pública, 2017)
OBJECTIVE To analyze the quality of records for live births and infant deaths and to estimate the infant mortality rate for skin color or race, in order to explore possible racial inequalities in health. METHODS Descriptive study that analyzed the quality of records of the Live Births Information System and Mortality Information System in Rondônia, Brazilian Amazonian, between 2006-2009. The infant mortality rates were estimated for skin color or race with the direct method and corrected by: (1) proportional distribution of deaths with missing data related to skin color or race; and (2) application of correction factors. We also calculated proportional mortality by causes and age groups. RESULTS The capture of live births and deaths improved in relation to 2006-2007, which required lower correction factors to estimate infant mortality rate. The risk of death of indigenous infant (31.3/1,000 live births) was higher than that noted for the other skin color or race groups, exceeding by 60% the infant mortality rate in Rondônia (19.9/1,000 live births). Black children had the highest neonatal infant mortality rate, while the indigenous had the highest post-neonatal infant mortality rate. Among the indigenous deaths, 15.2% were due to ill-defined causes, while the other groups did not exceed 5.4%. The proportional infant mortality due to infectious and parasitic diseases was higher among indigenous children (12.1%), while among black children it occurred due to external causes (8.7%). CONCLUSIONS Expressive inequalities in infant mortality were noted between skin color or race categories, more unfavorable for indigenous infants. Correction factors proposed in the literature lack to consider differences in underreporting of deaths for skin color or race. The specific correction among the color or race categories would likely result in exacerbation of the observed inequalities.